Effect of gravity on liquefaction behavior - R. Sukhumkitcharoen; J. Koseki; M. Otsubo; T. Morimoto (Soils and Foundations, 2025)
Attaining a fully liquefied state with zero effective stress in laboratory element tests is inherently challenging, as this state is typically achieved only in the upper layers of specimens, while the lower layers are still influenced by residual gravitational forces (or self-weight). This challenge has highlighted concerns regarding the potential overestimation of the liquefaction resistance in laboratory-based assessments. In response to this, the present study introduces an advanced bi-axial apparatus designed for testing under both dry and submerged conditions, employing circular plastic rods to enable an analysis with detailed images. Furthermore, discrete element method (DEM) simulations are conducted to replicate analogous environments under varying gravity conditions. The results demonstrate that the configuration of the apparatus, which utilizes lighter materials, significantly diminishes the gravity-induced stress gradient, achieving near-zero effective mean stress in the submerged condition. Both laboratory tests and DEM simulations consistently show similar trends under different gravity settings, such as enhanced contractive behavior, reduced remaining mean stress, and reduced remaining stiffness during the liquefied state in lower gravity environments, resulting in a reduction in liquefaction resistance. These characteristics are attributed to the stimulated loss of inter-particle contacts and an increased number of unstable particles, resulting in weakened void- and contact-based fabrics against cyclic loading under lower gravity conditions. Based on the current testing conditions, a correction factor of approximately 0.6 to 0.8 is advised for bi-axial tests conducted at standard gravity (1g) to convert the liquefaction resistance measured in the laboratory to that suitable for practical applications.